Direct observation of the CRAND proton radiation belt source. Issue 12 (4th December 2013) - Selesnick, R. S.; Hudson, M. K.; Kress, B. T.
<x xml:space="preserve">Abstract</x> [1] Observations of geomagnetically trapped 27–45 MeV protons following the November 2003 magnetic storm show a gradual intensity rise that is interpreted as a direct measurement of the cosmic ray albedo neutron decay (CRAND) source strength. The intensity rise is simulated by combining the detector response function with a model CRAND source, obtained by drift‐averaging neutron intensity from Monte Carlo simulation of cosmic ray interactions in the atmosphere. The simulation, for 2.4<L<2.7, matches the data within statistical uncertainties, verifying the CRAND model. Another simulation includes the effects of solar proton trapping and other known radiation belt processes. It further shows that the CRAND source was predominant, while radial diffusion and magnetic storm losses effected minor corrections in certain L ranges.